Pengecekan Tingkat Hemoglobin pada Mahasiswa Universitas Halu Oleo Sebagai Upaya Identifikasi Risiko Anemia - Sukmawati Sukmawati; Irma Yunawati; Nurnashriani Jufri; Wa Ode Salma; Vera Wati; Nurhasnah Said; Hafizah Aulia; Ajiza Ariani; Ferlin Dwipuspita Sari; Radya Permala Dewi (Inovasi Kesehatan Global, 2025)
Hemoglobin (Hb) is a protein that functions to transport oxygen and carbon dioxide in the blood. Anemia, caused by iron deficiency, can affect physical health and academic performance, particularly in adolescents and students. Factors such as diet, habits, and socio-economic status contribute to the incidence of anemia. Anemia can lead to fatigue, reduced concentration, and decreased physical endurance. Therefore, improving nutritional status is crucial to support health and academic achievement.